Two new genera and two new species of cicadas from Central America (Hemiptera: Cicadidae: Cicadinae) - Sanborn, Allen F. (Zootaxa, 2018)
New Neotropical cicada genera and species are described. Dazollina petilunca n. gen., n. sp. (Zammarini: Dazina) is described from Costa Rica and Guatemala, Muraoides costaricensis n. gen., n. sp. (Hyantiini) is described from Costa Rica. An updated generic key to the Dazina and Hyantiini are provided.